Mathematical model of denamic deformation of compacted elastic viscous plastic medium - S. V. Saveliev; V. V. Mikheev; A. S. Beloded (Вестник СибАДИ)
The article is devoted to research of dynamic deformation of soil sealing process environment. An original approach to the modeling of the process. Sealing medium is regarded as elasticviscoelastic body, a deformable external periodic force. As the elements characterizing the rheological properties of such a medium, selected elements before it: Gooke, Newton and Saint-Venant. The model allows us to investigate the stress-strain state of the environment in the process of deformation of the entire thickness of up-lotnyaemogo layer. Implementation of the proposed modeling approach allows the rose-Sit seal the energy efficiency of the process, select the modes of rational flow of the process and the parameters of the compactor.